Choroidal Morphologic and Vascular Features in Patients With Myopic Choroidal Neovascularization and Different Levels of Myopia Based on Image Binarization of Optical Coherence Tomography - Wang, Xinglin; Yang, Jiarui; Liu, Yushi; Yang, Luling; Xia, Huaqin; Ren, Xiaotong; Hou, Qingyi; Ge, Yimeng; Wang, Changguan; Li, Xuemin (Frontiers in Medicine, 2022)
Purpose: To characterize the choroidal morphologic and vascular features in different levels of myopes and patients with myopic choroidal neovascularization (mCNV). Methods: A total of 148 subjects were enrolled in this cross-sectional study, including 78 low-to-moderate myopes (LMM), 53 high myopes (HM) and 17 high myopic patients with mCNV. Ocular biometrics were measured using an optical low-coherence reflectometry device. Retinal and choroidal imaging was performed using enhanced depth imaging spectral domain optical coherence tomography. Retinal parameters including retinal thickness and retinal volume were obtained from a built-in software. Binarization technique was adopted to investigate choroidal parameters including choroidal thickness (CT), vascular area, stromal area and choroidal vascularity index (CVI). Choroidal parameters were measured at five locations to cover as much area of choroid as possible, and their patterns of distribution were further analyzed. Results: Patients with mCNV had an atrophic retina of comparable thickness to HM (273.65±17.28 vs 276.49±13.29, μm, p=0.47), but the choroid was thinner than that of HM (153.94±15.12 vs 236.09±38.51, μm, p<0.001). Subfoveal CVI was greatest in the mCNV eyes (0.651 ± 0.009), followed by HM (0.645 ± 0.012) and LMM eyes (0.636 ± 0.012). Similar to CT, CVI was also found significantly different among these three groups at all five locations (p for trend <0.001 for all locations). AL was negatively correlated with retinal volume (r=-0.236, p=0.009), which is the only significant finding in associations between ocular factors and retinal parameters. Strong, negative correlations were identified between axial length (AL) and subfoveal choroidal thickness (SFCT, r=-0.820, p<0.001). However, AL was positively correlated with subfoveal CVI (r=0.668, p<0.001). CVI was greater in myopic eyes with thinner choroid (r=-0.578, p<0.001). BCVA exhibited no significant association with CVI (r=0.139, p=0.092), but was negatively correlated with SFCT (r=-0.386, p<0.001) and positively correlated with AL (r=0.351, p<0.001). Conclusion: Choroid in patients with mCNV was thinner yet more vascularized than that in HM and LMM subjects. CVI increased with a longer AL which was associated with a smaller SFCT, choroidal vascular area (VA) and total choroidal area (TCA). Better BCVA was achieved in subjects with thicker SFCT and shorter AL.